Accessible web indexes: design for those with disabilities. (March 2017) - Caballero, Cheryl; Guldner, Rosalind
Abstract : To comply with new regulations, indexers at the Ontario Legislature had to alter their production processes to make their online indexes accessible to visually impaired users. Cheryl Caballero and Rosalind Guldner explain how they tackled the requirement, with results, they believe, beneficial to all Ontario Hansard users.